2011
DOI: 10.2106/jbjs.k.01021
|View full text |Cite
|
Sign up to set email alerts
|

Use of Patient-Reported Outcomes in the Context of Different Levels of Data*

Abstract: There is increasing interest in measuring patient-reported outcomes as part of routine medical practice, particularly in fields like total joint replacement surgery, where pain relief, satisfaction, function, and health-related quality of life, as perceived by the patient, are primary outcomes. We review some well-known outcome instruments, measurement issues, and early experiences with large

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 26 publications
0
76
1
Order By: Relevance
“…For example, annual, aggregate PROMs for total hip replacement care in every hospital in Sweden are publicly reported and compared and are an integral aspect of the national and regional quality monitoring programs. 25 In the United States, CMS began public reporting of riskadjusted 30-day readmissions and 90-day all cause complications after TJR by hospital in 2013 and 2014, respectively, and efforts are underway to evaluate the inclusion of PROMs as part of overall quality monitoring. 26 Both the National Quality Foundation and CMS endorse the use of PROMs for quality monitoring and in value payment programs.…”
Section: Use 2 Value To Hospital Leaders and Cliniciansmentioning
confidence: 99%
“…For example, annual, aggregate PROMs for total hip replacement care in every hospital in Sweden are publicly reported and compared and are an integral aspect of the national and regional quality monitoring programs. 25 In the United States, CMS began public reporting of riskadjusted 30-day readmissions and 90-day all cause complications after TJR by hospital in 2013 and 2014, respectively, and efforts are underway to evaluate the inclusion of PROMs as part of overall quality monitoring. 26 Both the National Quality Foundation and CMS endorse the use of PROMs for quality monitoring and in value payment programs.…”
Section: Use 2 Value To Hospital Leaders and Cliniciansmentioning
confidence: 99%
“…National registries that collect data from hospitals only to estimate revision rates must assure that all hospitals participate or some revisions will be missed. Recently, a subset of national registries (England and Wales, New Zealand) began to collect PROs directly from patients [9]. However, this process has different challenges and limitations.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…A recent review of the use of PROs in registries concluded: ''omitting patient-reported outcomes precludes us [surgeons] from having a full understanding of the factors that contribute to pain relief, restoration of function, and patient satisfaction'' [20].…”
Section: Where Are We Now?mentioning
confidence: 99%
“…PROs also capture presence of persistent pain and unsatisfactory functional gains in patients who fail to achieve the desired outcome. Some of the international TJA registries now incorporate PROs that emphasize the patient's perception of pain and physical function [20], and recent evidence-based research has called attention to the value of incorporating PROs in national joint registries [19].…”
Section: Introductionmentioning
confidence: 99%